HIGHER FREQUENCY OF GERMINAL MATRIX-INTRAVENTRICULAR HEMORRHAGE IN MODERATE AND LATE PRETERM AND EARLY TERM NEONATES WITH INTRAUTERINE GROWTH RESTRICTION COMPARED TO HEALTHY ONES/VECA UCESTALOST PERIVENTRIKULSKOG-INTRAVENTRIKULSKOG KRVARENJA KOD UMJERENE I KASNE NEDONOSCADI I RANE TERMINSKE NOVORODENCADI S INTRAUTERINIM ZASTOJEM U RASTU U ODNOSU NA ZDRAVU NOVORODENCAD - Mileusnic-Milenovic, Radmila (Acta clinica Croatica (Tisak), 2021)
Germinal matrix-intraventricular brain hemorrhage is mostly found in preterm neonates, but may also occur in term neonates. The aim of this study was to analyze the prevalence and severity of this type of hemorrhage in moderate and late preterm and early term neonates with intrauterine growth restriction. In the prospective analysis, 100 newborns were examined, i.e. 70 with intrauterine growth restriction and 30 as a control group. Study subjects were neonates from 32 0/7 to 38 6/7 gestational weeks. Body weight, body length, head circumference and ponderal index at birth were analyzed. Hemorrhage was assessed by cranial ultrasound using Papile classification. Out of 70 neonates with intrauterine growth restriction, germinal matrix-intraventricular hemorrhage was not found in 36 (51.43%) neonates, 31 (44.29%) had hemorrhage grade 1, and three (4.29%) had hemorrhage grade 2, which was statistically significant (p<0.001) in relation to the control group. There were no neonates with hemorrhage grade 3 or 4. The predominant type of germinal matrix-intraventricular hemorrhage in the intrauterine growth restriction group was hemorrhage grade 1. Germinal matrixintraventricular hemorrhage was more often present in the intrauterine growth restricted neonates than in the control group. Key words: Neonates; Growth restriction; Germinal matrix-intraventricular hemorrhage; Cranial ultrasound Periventrikulsko-intraventrikulsko krvarenje u mozgu uglavnom se nalazi u nedonoscadi, ali se takoder moze pojaviti kod djece rodene u terminu. Cilj ovog istrazivanja bio je analizirati ucestalost i ozbiljnost ovog tipa krvarenja kod umjerene i kasne nedonoscadi i rane terminske novorodencadi s intrauterinim zastojem u rastu. U prospektivnoj analizi ispitano je 100 novorodencadi: 70 s intrauterinim zastojem u rastu i 30 kao kontrolna skupina. Ispitanici su bili novorodencad od 32 0/7 do 38 6/7 tjedana gestacije. Analizirana je tjelesna tezina, duljina tijela, opseg glave i ponderalni indeks pri rodenju. Krvarenje je odredeno klasifkacijom Papile, uz pomoc ultrazvucne pretrage mozga. U 36 (51,43%) od 70 novorodencadi s intrauterinim zastojem u rastu nije pronadeno periventrikulsko-intraventrikulsko krvarenje, 31 (44,29%) je imalo krvarenje 1. stupnja, dok ih je 3 (4,29%) imalo krvarenje 2. stupnja, sto je bilo statisticki znacajno (p<0,001) u odnosu na kontrolnu skupinu. Nije bilo novorodencadi s krvarenjem 3. ili 4. stupnja. Dominantni tip periventrikulskog-intraventrikulskog krvarenja u skupinama umjerene i kasne nedonoscadi i rane terminske novorodencadi s intrauterinim zastojem u rastu bilo je krvarenje 1. stupnja. U novorodencadi s intrauterinim zastojem u rastu periventrikulsko-intraventrikulsko krvarenje zabiljezeno je cesce u odnosu na kontrolnu skupinu. Kljucne rijeci: Novorodencad; Zastoj u rastu; Periventrikulsko-intraventrikulsko krvarenje; Ultrazvuk mozga